READING THE LANGUAGE OF BUILDINGS: THE ROLE OF SEMIOTICS IN ARCHITECTURAL VISUAL COMMUNICATION - Ayub Muktiono (Jurnal Multidisiplin Sahombu, 2023)
As a medium of communication, buildings communicate in a language that not everyone can understand. Other communication media are needed so that the language used in the form of buildings can be translated into a language that is more easily understood by many people. Visuals are one of them. Semiotics, as the study of signs and meaning, is a theoretical basis for understanding how architectural elements can be interpreted as visual messages that convey information and experience. The aim of this research is to explore how semiotics can provide deeper insight into the process of reading and interpreting building language. The results of this research reveal that semiotics has an integral role in understanding building language and architectural visual communication. In analyzing elements such as shape, color, and space, semiotics helps identify symbols and signs that convey complex messages regarding cultural identity, function, and meaning. This research also highlights that semiotics is not just an analytical tool, but rather the key to developing an effective and meaningful building language, enabling architects to design buildings with elements that clearly convey the desired meaning. In conclusion, semiotics plays a central role in enriching the interpretation of every aspect of architectural design, making buildings not only as physical structures, but also as deep and telling visual narratives.